Four decades of mapping and quantifying neuroreceptors at work in vivo by positron emission tomography - Gjedde, Albert; Wong, Dean F. (Frontiers in Neuroscience, 2022)
The decryption of brain images is the basis for the necessary translation of the findings from the imaging to information that is useful to the demands of clinical intervention. Agents of brain imaging must meet the requirements dictated by the need for interpretation in terms of diagnosis and prognosis. In addition, the agents must serve as fundamental research tools that meet the requirements for understanding new therapeutic drugs, including compounds as diverse as antipsychotics, antidepressants, and anxiolytics, and drugs serving the relief of symptoms from neurological disorders as unrelated as multiple sclerosis, stroke, and dementia. Here we review and explain the kinetics of methods that enable researchers to describe the brain’s work and functions. The methods are approaches that neurokineticists invented and expanded upon during decades of experimental work, and the methods are particularly useful to the prediction of possible future approaches to the treatment of brain disorders. We provide an overall description of the basic elements of kinetics and the underlying methods of quantification, as well as the mathematics of modeling the recorded brain dynamics embedded in images obtained in vivo. The presentation is necessary to justify the contribution of modeling to the development of methods, and to support the specifications for the proposed use in clinical settings. The processes of quantification and kinetic modeling are equally essential to image reconstruction and labeling of brain regions of structural or functional interest. The procedures presented here are essential tools of scientific approaches to all conventional and novel forms of brain imaging. The foundations of the kinetic and quantitative methods are keys to the satisfaction of clinicians that actively engage in the treatment of the disorders of mammalian brains in the fields of neurology, neurosurgery, and neuropsychiatry.